150k views
0 votes
Solve for n.
11(n — 1) + 35 = 3
On = 6
0 1 = -3
On = 3
On= 6

User Neilmarion
by
6.0k points

2 Answers

5 votes

Answer:

n = -21/11

Explanation:

11(n - 1) + 35 = 3

Expand the brackets.

11n - 11 + 35 = 3

Add the terms -11 and 35.

11n + 24 = 3

Subtract 24 on both sides.

11n = 3 - 24

Subtract.

11n = -21

Divide 11 into both sides.

n = -21/11

User Kevin Brown
by
5.5k points
3 votes

Answer:


n = - (21)/(11) \\

Explanation:


11(n - 1) + 35 = 3 \\ 11n - 11 + 35 = 3 \\ 11n + 24 = 3 \\ 11n = 3 - 24 \\ 11n = - 21 \\ (11n)/(11) = ( - 21)/(11) \\ n = - (21)/(11)